Pharmacoeconomic study of the treatment of arterial hypertension in children and adolescents using cost-of-illness analysis - O. S. Mikhaylova; A. V. Krikova (IRBIS LLC, 2022)
Background. The cost-of-illness (COI) analysis allows to estimate and plan costs for calculations between the subjects of the health care system and medical insurance organizations. The primary morbidity of the population with diseases of the circulatory system increased from 4,784 thousand people in 2018 to 5,136 thousand in 2019. A growth in the number of cases resulted in an increase in the demand for drugs for the treatment of cardiovascular diseases.Objective: to perform a pharmacoeconomic study of the treatment of arterial hypertension in children and adolescents by COI-analysis.Material and methods. The source of information for COI-analysis was the real clinical practice - medical records of sick children and adolescents. A pharmacoeconomic study using COI-analysis was carried out at the inpatient and outpatient stages of care and included the calculation of direct medical costs (the costs of laboratory, instrumental medical services, non-drug and drug antihypertensive therapy). The study included 102 children diagnosed with arterial hypertension. The average stay of patients in the hospital was 10 (10.4±0.35) bed-days and treatment on an outpatient basis varied from 3 months to 1 year.Results. The leading place in the structure of costs for antihypertensive therapy is occupied by the beta-blockers pharmacological group (35%). The total cost of arterial hypertension in children and adolescents in inpatient and outpatient settings was 4,459.00 and 29,638.90 rubles, respectively.Conclusion. The COI-analysis of arterial hypertension confirms the need for timely diagnosis and treatment and preventive measures for high blood pressure in children and adolescents to reduce the development of risk factors for such serious cardiovascular complications as stroke and myocardial infarction in adulthood, the treatment of which requires large cash costs.